Implementation of the Gayo Lues Regent's Regulation Policy Number 12 of 2016 concerning the Management of Property of Gayo Lues Regency (Four Wheel Service Vehicle Auction Study) - Ependi, Rustam; Kusmanto, Heri; Adam, Adam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The aims of this study is to find out the Implementation of the Gayo Lues Regent's Regulation Policy Number 12 of 2016 concerning the Management of Property of Gayo Lues Regency. This study used a qualitative approach. The result show that The implementation of the Gayo Lues Regent's Regulation Number 12 of 2016 concerning the Management of Gayo Lues Regency Property (Four Wheel Service Vehicle Auction Study) has been carried out well but has not run perfectly. This can be seen from the results of the analysis of George Edward III's Theory as follows: Communication. The auction of four-wheeled official vehicles carried out by the Financial Management Agency of Gayo Lues Regency has been carried out through auction announcements through print and electronic mass media as well as providing direct information for the people who come and for goods to be auctioned which are still controlled by the head of the SKPK, a correspondence has been made written by Mr. Sekda as district property manager.